2021
DOI: 10.3390/brainsci11060790
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Severe Suicidality and Nonsuicidal Self-Injury Behaviors in Bipolar Adolescents Referred to a Psychiatric Emergency Unit

Abstract: Background: Severe suicide ideation or attempts and non-suicidal self-injury (NSSI) present both differences and relevant overlaps, including frequent co-occurrence and shared risk factors. Specific categorical diagnoses, namely bipolar disorder (BD), may affect clinical features and natural histories of suicidal or not suicidal self-harm behaviour. Our study aimed to compare suicidality (severe suicidal ideation or suicidal attempts) and NSSI in referred bipolar adolescents. Methods: The sample included 95 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…To deepen possible elements associated with an increased risk of sever suicide ideation and attempts, internalizing disorder and adverse childhood experiences emerged as significant risk factors, consistent with the literature data and our previous findings [10,39,40]. Regarding age and gender differences, our findings are consistent with prior studies, which showed that suicide attempts are more common in adolescent females.…”
Section: Discussionsupporting
confidence: 92%
“…To deepen possible elements associated with an increased risk of sever suicide ideation and attempts, internalizing disorder and adverse childhood experiences emerged as significant risk factors, consistent with the literature data and our previous findings [10,39,40]. Regarding age and gender differences, our findings are consistent with prior studies, which showed that suicide attempts are more common in adolescent females.…”
Section: Discussionsupporting
confidence: 92%
“…The reason why the results of this study were higher than those of previous studies may be due to the differences in the criteria for defining and measuring NSSI. For example, in Tang et al's study, the criterion for self-injury was defined as “occurring more than 5 times per year”, whereas in Martin et al's study, the instrument used to measure NSSI was a question that asked, “During the past 12 months, how many times did you do something to purposely hurt yourself without wanting to die, such as cutting or burning yourself on purpose?” The prevalence of NSSI is higher in girls than in boys, which is the same as previous studies [ 50 , 51 ]. Previous research has shown [ 52 ] that men are more likely to take direct action, i.e., action to change the problem, in response to life events than women, so that when faced with negative life events, boys are more likely to take action to solve the problem, whereas girls may need more time to deal with these negative life events.…”
Section: Discussionsupporting
confidence: 90%
“…According to this theory, the occurrence of NSSI is not intended for suicide purposes; however, NSSI is closely related to SI, AS, and SB ( Hawton et al, 2003 ; Nock et al, 2008 ; Martin et al, 2010 ), where NSSI frequency, number of self-injury methods, and hopelessness are the strongest predictors of AS ( Victor and Klonsky, 2014 ; Coppersmith et al, 2017 ). Notably, NSSI is a risk factor for committing suicide among adolescents with depression ( Hawton et al, 2003 ; Zubrick et al, 2017 ; Fan et al, 2021 ; Masi et al, 2021 ). In particular, female adolescents have a higher risk of committing suicide if they exhibit frequent NSSI behaviors ( You and Lin, 2015 ).…”
Section: Discussionmentioning
confidence: 99%